A study on demulsification of stable water-in-crude oil emulsions : chemical and microwave approach - 426530 Zulkifly Jemaat (Skudai : Universiti Teknologi Malaysia, 2006)
Thesis (Sarjana Kejuruteraan (Kimia)) - Universiti Teknologi Malaysia, 2006